Quantitative phase analysis in the assessment of coronary artery disease. Issue 1 (January 1989) - Underwood, S R; Walton, S; Laming, P J; Ell, P J; Emanuel, R W; Swanton, R H
Abstract : The phase image in radionuclide ventriculography shows the timing of ventricular contraction and is valuable in the detection of abnormalities induced by coronary artery disease. The image is usually interpreted subjectively, and in the present study a histogram of left ventricular phase values was used to make interpretation more objective. The left ventricular ejection fraction and the standard deviation, skewness, and kurtosis of the phase histogram were measured at rest, during isometric exercise, and during the final two stages of maximal dynamic exercise in 25 controls and 27 patients with coronary artery disease without previous infarction. The ejection fraction and the standard deviation of the phase had the same predictive accuracy for the presence of disease when measured during the penultimate stage of dynamic exercise (89%) as during the final stage, but their accuracy was lower during maximal exercise (77%) because of motion artefact at high exercise levels. Skewness and kurtosis of the histogram were of no value for the detection of disease, and isometric exercise was of only limited value. It is concluded that the phase histogram provides an objective measurement of the synchronicity of left ventricular contraction and can increase sensitivity for the detection of abnormality. Data should be acquired at all stages of dynamic exercise, and the penultimate stage should be used if there is any doubt about the validity of the final stage.